Measuring English Language Education Department Students’ Speaking Fluency Level - Sendi Winaryo; Rosalin Ismayoeng Gusdian (Wanastra: Jurnal Bahasa dan Sastra, 2021)
This research aimed at investigating English Language Education department students’ speaking fluency level. The research subjects were twelve third-semester students of English Language Education Department at the University of Muhammadiyah Malang. Mixed method was used in this research. The data were collected in the form of audio transcription. Three fluency standards were used, namely speech rate, pause rate, and disfluent syllable. The result showed that all of the students obtained the disfluent syllable, with a score below 30 disfluencies per minute. The majority of students obtained a low level of speaking fluency in terms of speech rate and pause rate. The average of students’ speech rate was below 162 syllables per minute and the majority of students’ pause rate was above 1 second. In conclusion, two students achieved level 3 (good) of speaking fluency and ten other students achieved level 2 (intermediate). Key Word: English language education students, fluency level, speaking